#### Answer

$f^{-1}(x) = \sqrt[3] {\frac{x - 5}{-4}}$

#### Work Step by Step

$f(x) = 5 - 4x^{3}$
$y = 5 - 4x^{3}$
$y - 5 = -4x^{3}$
$\frac{y - 5}{-4} = x^{3}$
$\sqrt[3] {\frac{y - 5}{-4}} = x$
$f^{-1}(x) = \sqrt[3] {\frac{x - 5}{-4}}$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(x) = \sqrt[3] {\frac{x - 5}{-4}}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.